Respuesta :
Answer:
Option C is correct.
Step-by-step explanation:
The x-intercepts of the function (x − 1)(x − 4)(x + 7) can be found by putting this function equal to zero
(x − 1)(x − 4)(x + 7) = 0
Now,
x-1 = 0
x-4 = 0
and x+7 = 0
Now finding the values of x
x-1 = 0 + 1
x - 1 + 1 = 1
=> x = 1
or (1,0)
x - 4 = 0
x -4 + 4 = 0 + 4
x = 4
or (4,0)
x + 7 = 0
x +7 -7 = 0 -7
x = -7
or (-7,0)
SO, the x-intercepts of the function (x − 1)(x − 4)(x + 7) are (1,0),(4,0) and (-7,0)
Option C is correct.
Answer:
+ 1 + 4 -7
Step-by-step explanation:
when they ask for x intercepts you simply have to set the function to 0 and then solve for x or in other words just reverse the number for example. here we have -1 -4 and +7 so just reverse the negative and positive signs